2002
DOI: 10.1530/rep.0.1230269
|View full text |Cite
|
Sign up to set email alerts
|

Role of FSH, numbers of FSH receptors and testosterone in the regulation of inhibin secretion during the seasonal testicular cycle of adult rams

Abstract: The regulation of inhibin secretion has not been elucidated fully in male ruminants. The aim of this study was to determine the relative importance of FSH and testosterone concentrations, and FSH receptors, in the control of secretion of immunoactive inhibin in rams. In Expt 1, temporal changes in hormone concentrations and testicular FSH binding were determined for two groups of rams (n = 4) kept under opposite, alternating 4 month periods of long (16 h light:8 h dark) and short (8 h light:16 h dark) days. Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…As previously demonstrated for several different hormones (Xiao and Goff 1999;Sanford et al 2002), GnRH-R in Podarcis is up-regulated by its ligand. Our in vitro experiments demonstrate that, following cGnRH II treatment, the number of pyriforms positive for the receptor antibody markedly increases.…”
Section: Discussionsupporting
confidence: 66%
“…As previously demonstrated for several different hormones (Xiao and Goff 1999;Sanford et al 2002), GnRH-R in Podarcis is up-regulated by its ligand. Our in vitro experiments demonstrate that, following cGnRH II treatment, the number of pyriforms positive for the receptor antibody markedly increases.…”
Section: Discussionsupporting
confidence: 66%
“…Not only the average serum concentrations of gonadotropins but also the frequency of LH pulses decline sharply as the testes regress (Sanford et al, 1974(Sanford et al, , 2002Fig. 4).…”
Section: Seasonal Changes In Neuroendocrine Regulation Of the Testismentioning
confidence: 99%
“…Carlsen et al (1999) found a significant diurnal variation in serum inhibin B levels in normal men, lacking evidence for a role of FSH. However, the covariation with serum concentrations of testosterone and estradiol suggested that these hormones might play a role in the diurnal rhythm of inhibin B, although some other common influences could not be excluded (Sanford et al, 2002). Comhaire et al (1995), using an alpha subunit assay, recorded a similar diurnal variability in serum inhibin, and so did Kamischke et al (2001).…”
Section: Discussionmentioning
confidence: 97%